2009
DOI: 10.1186/1471-2458-9-382
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of parental and school personnel smoking to health risk behaviours among Finnish adolescents

Abstract: BackgroundThis study compared parental smoking with school personnel smoking in relation to adolescents' smoking behaviours, alcohol use, and illicit drug use.MethodsA cross-sectional survey for 24,379 adolescents was linked to a survey for 1946 school employees in 136 Finnish schools in 2004-2005. Surveys included smoking prevalence reported by school staff, adolescents' reports of school staff and parental smoking, adolescents' own smoking behaviours, alcohol use, and illicit drug use. Multilevel analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 41 publications
0
22
2
1
Order By: Relevance
“…This may due to the reduction of family influence on adolescents as they grow older and their first and second hand exposure to the adverse effects of smoking may make smoking less appealing to them. The findings of this study however is not consistent with results reported from Kleinjan et al (2009) andVirtanen et al (2009) who found a lower likelihood of the intention to cease smoking among adolescents whose parents were smokers. Brown et al (2010) also reported that siblings who smoked was one of the predictors to future smoking intention among adolescents.…”
Section: Discussioncontrasting
confidence: 99%
“…This may due to the reduction of family influence on adolescents as they grow older and their first and second hand exposure to the adverse effects of smoking may make smoking less appealing to them. The findings of this study however is not consistent with results reported from Kleinjan et al (2009) andVirtanen et al (2009) who found a lower likelihood of the intention to cease smoking among adolescents whose parents were smokers. Brown et al (2010) also reported that siblings who smoked was one of the predictors to future smoking intention among adolescents.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, smoking prevention should be aimed at young people (5,6). Children and adolescents learn smoking from their role models (7). Given that teachers are respected people, they have a great responsibility for tobacco control (8).…”
Section: Introductionmentioning
confidence: 99%
“…We found that teachers smoking in the presence of students are related to smoking onset. Similarly to previous studies (Murray, Kiryluk, y Swan, 1984;de Moor et al, 1992), there was no correlation between the percentages of teachers and students that smoked but a study in Finland (Virtanen et al, 2009) showed a discreet association. Interestingly, a study performed in 1979 showed a close association between smoking by teachers and adolescents (Bewley, Johnson, y Banks, 1979), but this may have been due to a strong correlation between smoking in front of students and percentage of smoking teachers at that time.…”
Section: Discussionmentioning
confidence: 60%